1991
DOI: 10.1083/jcb.113.3.623
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of acetylcholine receptor subunit assembly and its regulation by cAMP.

Abstract: Abstract. Assembly of nicotinic acetylcholine receptor (AChR) subunits was investigated using mouse fibroblast cell lines stably expressing either Torpedo or mouse (AM-4) a, ~, % and ~ AChR subunits. Both cell lines produce fully functional cell surface AChRs. We find that two independent treatments, lower temperature and increased intracellular cAMP can increase AChR expression by increasing the efficiency of subunit assembly. Previously, we showed that the rate of degradation of individual subunits was decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
41
0
3

Year Published

1992
1992
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(52 citation statements)
references
References 38 publications
8
41
0
3
Order By: Relevance
“…Furthermore, the majority of internal ␤ 2 protein co-localizes with calnexin, an ER-resident protein. This is consistent with previous studies of muscle nAChR, where it has been shown that the limiting step of surface expression appears to be at the ER (36,37). At the ER, there are several potential steps in receptor biosynthesis that could be regulated by nicotine to affect expression levels.…”
Section: Discussionsupporting
confidence: 81%
“…Furthermore, the majority of internal ␤ 2 protein co-localizes with calnexin, an ER-resident protein. This is consistent with previous studies of muscle nAChR, where it has been shown that the limiting step of surface expression appears to be at the ER (36,37). At the ER, there are several potential steps in receptor biosynthesis that could be regulated by nicotine to affect expression levels.…”
Section: Discussionsupporting
confidence: 81%
“…This indicates that intracellular ␣␤ 128 ␥␦ complexes are similar in size and composition to intracellular ␣␤␥␦ complexes with the exception of the ␣ 2 ␤␥␦ complexes in the 9 S peak. The broad profile observed for the intracellular AChR complexes relative to the cell surface ␣ 2 ␤␥␦ 9 S peak has been seen in other studies both for the Torpedo subunits at reduced temperature (4,8,40) and the mouse subunits at 37°C (3,5,6,8). D, the effects of the ␣ 128/142 and ␤ 128 subunits on subunit assembly are consistent with the model shown.…”
Section: Elimination Of Cystine Loop Disulfide Bond On the ␣ Subunit supporting
confidence: 77%
“…Interestingly, it has been demonstrated that both the ␥ and ␦ subunits are phosphorylated in vivo, and the ␦ subunits are more highly phosphorylated in the unassembled than in the assembled state indicating that phosphorylation precedes assembly and that phosphorylation/dephosphorylation mechanisms control the AChR subunit (36). Furthermore, using Torpedo AChR subunits expressed in mouse fibroblasts, it has been demonstrated previously that cAMP-induced increase in expression of cell surface AChRs is due to phosphorylation of the unassembled ␥ subunit assembly (37). But the underlying mechanism by which this phosphorylation increases the efficiency of subunit assembly and increased surface AChR expression has not been elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…In muscle-type AChRs, pulse-chase experiments and immunofluorescent microscopy indicate that AChR subunit assembly is complete in the ER following which AChR oligomers move rapidly through the Golgi membrane onto the plasma membrane (37). Interestingly, it has been demonstrated that both the ␥ and ␦ subunits are phosphorylated in vivo, and the ␦ subunits are more highly phosphorylated in the unassembled than in the assembled state indicating that phosphorylation precedes assembly and that phosphorylation/dephosphorylation mechanisms control the AChR subunit (36).…”
Section: Discussionmentioning
confidence: 99%